From Macao to the United States and Canada: A Transnational Journey of Longing for Belonging - Tavares, Vander (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2022)
Framed as a narrative inquiry, this investigation focuses on the lived experiences of Seth, a 24-year-old international student from Macao at a university in Ontario prior to the pandemic. Semi-structured interviews were employed to explore the participant’s experiences of belonging and identity formation over the course of his transnational journey. Seth’s story highlights the importance of meaningful social interaction for the sociocultural adjustment and academic performance of international students. This paper provides insights into the needs of international students that may be useful for institutions of higher education as they continue to internationalize higher education and develop equity and inclusion-related strategies for international students.